CONDITIONS FOR DESIGNING THE SPECIAL COMPETENCES OF DIGITAL PEDAGOGUE-ANTHROPOLOGIST (Education in the 21st Century, 2023)
According to modern anthropologists, the program of phylogenetic development ofmankind's and the ontogenetic development of the individual presupposes a certain necessaryadaptation, which is conditioned by virtual reality, the latest technology, high technologies, onlinecommunication models, virtual organization leisure time. Without the mentioned points thesocialization of the person is impossible. According to digital pedagogical anthropologists, it istime to talk about the computer socialization of the learner, as a component of the general humansocialization process, to review the object of study of pedagogical anthropology, and thecorresponding educational paradigm.The problem. The rapid development of the digital pedagogical anthropological field on thebasis of techno anthropology leads to the development of a new specialization of digitalpedagogical anthropologist. The professional must have appropriate professional competencies,ensure the computer socialization of the learners, developing the virtual individual developmentmaps of the learner.The novelty of the research. The research provision is substantiated, according to which therapid development of digital pedagogical anthropological direction presupposes the formation of anew specialization - digital pedagogical anthropologists, who, having relevant professionalcompetencies, will carry out computer socialization of students in the context of generalsocialization. Digital pedagogical anthropologists predict that the object of study of pedagogicalanthropology will be the cyber human, and the subject - computer socialization.180The professional activity of a digital pedagogical anthropologist should be developed in twomain directions: social-humanistic and free-humanistic. The activities should be based on twomain principles: 1․complete research 2․principles of recording changes and regular analysisduring the development process.The conditions for developing the professional competencies of a digital pedagogicalanthropologist are:1. Transition from non-formal practical activity to formal professional theoretical-practicalactivity2. With appropriate qualification: training of digital pedagogical anthropologists3. Specification of the fields of activity of digital pedagogical anthropologists,4. Clarification of the functions of professional activity,5. Definition of rights and responsibilities of digital pedagogical anthropologists on the basisof relevant normative documents6. Use by digital educators-anthropologists of a range of valid pedagogical tools,7. Certification of digital educators-anthropologists in accordance with the improvement ofprofessional competencies.
Keywords: Digital pedagogue, anthropologist, computer scientist cialization, technoanthropology, anthropotechnomorphism, vir- total development map.